TANGGUNG JAWAB PERUSAHAAN ANGKUTAN TERHADAP PENGANGKUTAN BARANG MENGGUNAKAN JASA ANGKUTAN ORANG PADA PT. AYAH IBU TRANSPORT - Hamzah Hamzah; Zulfikar Jayakusuma; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The number of people who are still dependent on public transportation, the need for transportation will increasingly increase, causing more complex transportation problems, such transportation problems include transportation route licenses and regulations for these types of transportation modes are not matched by the provision of adequate public transportation, especially in terms of transportation capacity, not even a few of the public transport companies make these vehicles as service transportation and delivery of goods.This study uses a sociological juridical research method. This research was conducted in the city of Pekanbaru by taking data through interviews with PT Ayah Ibu Transport and also users of the transportation service. The collected data is analyzed qualitatively and deductive conclusions are drawn, that is, drawing conclusions from general to specific.The results of this study indicate that: First, the responsibilities of PT. Ayah Ibu Transport to the transport of goods using human transportation should have been able to be carried out by PT. Ayah Ibu Transport, because a civil engagement was born between the Bus Driver and also the owner of the goods. Unlawful Actions Bus Drivers who cause loss to the owner of the goods must be accounted for by PT Ayah Ibu Transport based on Article 1365 Civil Code, Article 193 Law No. 22 of 2009 concerning Traffic and Public Transportation and Article 19 of Law Number 8 of 1998 concerning Consumer Protection. Second, the factors that cause people to use passenger transportation services to send safekeeping goods are due to 3 (three) things, which are practical, cheaper costs and faster goods arrive. As for the advice of the author, first, To PT Ayah Ibu Transport to take control measures to the drivers who are responsible for driving the bus, so that safekeeping of goods alongside the road can no longer be done. Secondly, PT. Ladies and Gentlemen in order to use the services of PT. Ayah Ibu Transport by taking into account the provisions in force, so that losses can be minimized.Keywords: Transportation of Goods, Corporate Responsibility, Legal Protection